2018
DOI: 10.5194/hess-2018-299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of water management representations for watershed hydrologic modeling in the Yakima River Basin

Abstract: Abstract. Water management substantially alters natural regimes of streamflow through modifying retention time and water exchanges among different components of the terrestrial water cycle. Accurate simulation of water cycling in intensively managed watersheds, such as the Yakima River Basin (YRB) in the Pacific Northwest of the U.S., faces challenges in reliably characterizing influences of management practices (e.g., reservoir operation and cropland irrigation) on the watershed hydrology. Using the Soil and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The Soil and Water Assessment Tool (SWAT) hydrological model (Arnold et al, 2012) is a semi-distributed, time-continuous, and process-based river watershed model that allows assessment of the impact of land use and management on soil and streams in small to large watersheds. SWAT has been applied in several studies worldwide for watershed planning and management (Betrie et al, 2011;Gassman;Sadeghi;Srinivasan, 2014;Bressiani et al, 2015;Vigiak et al, 2016;Khelifa et al, 2017;Kaffas;Hrissanthou;Sevastas, 2018;Gharibdousti;Kharel;Stoecker, 2019;Qiu et al, 2019;Rafee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Soil and Water Assessment Tool (SWAT) hydrological model (Arnold et al, 2012) is a semi-distributed, time-continuous, and process-based river watershed model that allows assessment of the impact of land use and management on soil and streams in small to large watersheds. SWAT has been applied in several studies worldwide for watershed planning and management (Betrie et al, 2011;Gassman;Sadeghi;Srinivasan, 2014;Bressiani et al, 2015;Vigiak et al, 2016;Khelifa et al, 2017;Kaffas;Hrissanthou;Sevastas, 2018;Gharibdousti;Kharel;Stoecker, 2019;Qiu et al, 2019;Rafee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such perturbations in surface energy and water fluxes not only lead to surface cooling and decreases in Bowen ratios that modulate boundary layer evolution and convective processes in the atmosphere (DeAngelis et al, 2010; Harding & Snyder, 2012; Pei et al, 2016) but also influence the hydrologic budget. For example, previous studies (Leng et al, 2015; Qiu et al, 2019; Xu et al, 2019) have demonstrated that the hydrologic budget terms such as infiltration, percolation to deep soil layers, recharge to aquifers, and in turn baseflow at field, watershed, and large basin scales can be altered by irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the carbon and nitrogen fluxes and stocks in irrigated lands are expected to differ significantly from those in unirrigated lands (Follett, 2001). Irrigation is therefore an indispensable component of the water budget that can strongly modulate agro‐ecosystem dynamics and biogeochemical cycling in semiarid watersheds, although its contribution to watershed functioning has not been sufficiently studied (Brown, 2011; Qiu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%